2021
DOI: 10.1039/d0cp04493h
|View full text |Cite
|
Sign up to set email alerts
|

Singlet fission in naturally-organized carotenoid molecules

Abstract: We have investigated the photophysics of aggregated lutein/violaxanthin in daffodil chromoplasts. We reveal the presence of three carotenoid aggregate species, the main one composed of a mixture of lutein/violaxanthin absorbing...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…Carotenoids exhibit SF phenomena in H-aggregates and also in biological phases with significant disorder. , In J-aggregates, singlet fission is observed for dipolar carotenoids, although it has not been observed for nonpolar carotenoids . This apparent insensitivity to structural features of SF in carotenoids remains unexplained.…”
mentioning
confidence: 99%
“…Carotenoids exhibit SF phenomena in H-aggregates and also in biological phases with significant disorder. , In J-aggregates, singlet fission is observed for dipolar carotenoids, although it has not been observed for nonpolar carotenoids . This apparent insensitivity to structural features of SF in carotenoids remains unexplained.…”
mentioning
confidence: 99%
“…The SF in 1−4 and the parent DPH is much slower than that in (longer) diphenylpolyenes 26 and carotenoids. 30,31 In lutein and violaxanthin carotenoids, for example, a recent transient absorption study has revealed that excitation energy is transferred from S 2 to hot (higher vibrational levels of) S 1 in 150 fs, from which the conversion to 1 (TT) occurs within 1−2 ps. 31 Unlike in DPHs, no S 1 /S 2 equilibrium is achieved in the carotenoids before SF occurs from S 1 , which should be due to larger S 1 −S 2 energy gaps than in DPHs.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…SF has been reported in some kinds of molecular systems such as acenes, ,, polyenes, , carotenoids, isobenzofurans, and perylene diimides. The limited amount of SF-active molecules is mainly due to the restrictive list of requirements (the energetics and electronic coupling) necessary for a compound to be able to exhibit such a phenomenon. , To develop new SF materials with desired properties, namely the efficient SF and T 1 diffusion, it would be more realistic and effective to introduce suitable substituents onto the backbones of known SF-active molecules rather than trying to discover new candidate chromophores that fulfill the strict requirements. , …”
Section: Introductionmentioning
confidence: 99%
“…One strategy used to increase Δ E ST (and E T ) involves incorporation of a linearly conjugated polyene system, similar to those present in conventional SF materials including carotenes and arylated polyenes such as trans,trans,trans- 1,6-diphenylhexatriene (HT, Figure ). However, polyenes of this type undergo facile E–Z photoisomerization and [2+2] photocyclodimerization reactions.…”
Section: Introductionmentioning
confidence: 99%